ROLE OF BISPECTRAL INDEX AND SUPPRESSION RATIO MONITORING WITHIN THE EMERGENCY DEPARTMENT AFTER RETURN OF SPONTANEOUS CIRCULATION FOLLOWING CARDIAC ARREST?: A META-ANALYSIS. Issue 12 (18th November 2016) - Ramage, L; Simillis, C; Patil, S
Abstract : Objectives & Background: Prognostication following return of spontaneous circulation (ROSC) after cardiac arrest (CA) is of growing interest. Several studies have shown early use of the bispectral index (BIS) monitor to calculate the BIS and suppression ratio (SR) can be useful in predicting neurological outcome. This non-invasive technique can be initiated within the emergency department and used alongside other prognostication markers to help early decison-making. The aim of this meta-analysis is to assess early use of BIS and SR following CA to prognosticate neurologically favourable outcome measured using Cerebral Performance Category (CPC) score. Methods: Database searches of Pubmed, Web of Science and the Cochrane database were performed independently by two reviewers using the search terms: bispectral index, suppression-ratio, burst-suppression, prognostication, cardiac-arrest, return of spontaneous circulation. Papers included discussed early measurement (<24 hours) of BIS and/or SR following CA and prognostication of CPC outcomes at hospital discharge. Weighted means were calculated and compared using the independent T-samples test. Pooled sensitivity and specificity analysis was undertaken of BIS values. Results: 1524 records were returned; 967 were excluded based on title; 498 were excluded based on abstract, and 50 were excluded on manuscript review. 9 papers were included: 5 considered BIS index monitoring alone; 2 considered BIS and SR and 2 considered SR alone. The weighted means comparison of BIS within 24 hours of ROSC for patients with a CPC of 1–2 was 42.67+/−10.45 (n=175) versus 14.58+/−14.45 (n=197) in patients with a CPC category of 3–5 at discharge (p<0.0001). The pooled sensitivity, specificity, diagnostic odds ratio, and positive and negative likelihood ratios for early BIS monitoring were 70% (95% CI, 49%-85%), 93% (95% CI, 83%–97%), 30.42 (95% CI, 8.34–110.91), 9.74 (95% CI, 3.88–24.46), and 0.32 (95% CI 0.17–0.61) (figure 1). The weighted means comparison of SR measurements for patients with a CPC of 1–2 at discharge was 18.80+/−21.31% (n=94) versus 73.65+/−21.32% (n=90) in those with CPC 3–5 (p<0.0001). Conclusion: BIS and SR monitoring along with other markers may have a role as part of neuroprognostication within the emergency department. Further work is needed in the form of large scale trials.Figure 1 Table 1 Table 2 Table 3